Leading professional learning teams a start-up guide for improving instruction - Sather, Susan E.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2009)
Designed for school administrators, school leadership teams, and other teacher leaders, this resource provides essential guidelines for establishing effective professional learning teams (PLTs).
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Teachers -- In-service training; Professional learning communities; Teacher effectiveness; Effective teaching; Electronic books